'Because the baby asks for it': a mixed-methods study on local perceptions toward nutrition during pregnancy among marginalised migrant women along the Myanmar–Thailand border. Issue 1 (1st January 2018) - Hashmi, Ahmar H.; Paw, Moo Kho; Nosten, Suphak; Darakamon, Mu Chae; Gilder, Mary Ellen; Charunwatthana, Prakaykaew; Carrara, Verena I; Wickramasinghe, Kremlin; Angkurawaranon, Chaisiri; Plugge, Emma; McGready, Rose
ABSTRACT: Background : Under- and over-nutrition during pregnancy are known risk factors for pregnancy complications and adverse pregnancy and infant outcomes. Understanding perceptions around nutrition in pregnancy can create culturally appropriate interventions for improved health outcomes. Objective : A mixed-methods study was performed to explore local perceptions and practices of diet and physical activity in pregnancy in a marginalised population along the Myanmar–Thailand border. Methods : From April to July 2017, a cross-sectional survey and focus group discussions were conducted with pregnant women reporting to antenatal care; in-depth interviews were conducted with senior midwives at participating organisations along the Myanmar–Thailand border. Results : A total of 388 pregnant women were interviewed at two clinic sites along the Myanmar–Thailand border. A high proportion of women had limited knowledge of and poor dietary practices. Consuming a sweetened drink in the last 24 hours as well as being a non-teenage, multigravida woman was significantly associated with high body mass index (BMI) compared to normal BMI. Qualitative analysis combined focus group discussions (n = 66) and in-depth interviews (n = 4) summarising emergent themes: common foods eaten or avoided and rationale; benefits of nutrition; perceptions of overweight and weight gain during pregnancy; barriers to a healthy diet; and sources of diet information. Conclusions : There is limited awareness about healthy diets and lifestyle in these marginalised, migrant communities along the Myanmar–Thailand border. This study suggests that simple, culturally appropriate messaging should be provided to women and communities with low health literacy to generate awareness about healthy lifestyles and their effects on pregnancy outcomes as an important element of a broader strategy to address maternal nutrition in this population. However, more studies to determine the effectiveness of a broad range of interventions in low- and middle-income countries (LMIC) are needed, especially in marginalised migrant populations.